1978
DOI: 10.1007/bf02533755
|View full text |Cite
|
Sign up to set email alerts
|

Insect steroid metabolism

Abstract: Insects are unable to biosynthesize the steroid nucleus and generally require an exogenous source of sterols. Two salient areas of insect steroid metabolism are the dealkylation and conversion of dietary C28 and C29 plant sterols to cholesterol and other C27 sterols, and the biosynthesis and metabolism of the steroidal insect molting hormones. Certain azasteroids and nonsteroidal amines block this conversion of 24-alkyl sterols to cholesterol and/or disrupt molting and development in insects. These inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(49 citation statements)
references
References 44 publications
0
49
0
Order By: Relevance
“…as Manduca sexta, Tribolium confusum [5], HeZiothis zea [6], and Diatraea grandiosella [n, to name only a few representative species. It has also been shown that development in a number of species, including M .…”
Section: Introductionmentioning
confidence: 99%
“…as Manduca sexta, Tribolium confusum [5], HeZiothis zea [6], and Diatraea grandiosella [n, to name only a few representative species. It has also been shown that development in a number of species, including M .…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the structural requirements of other insects for sterols may vary depending upon the species [3,4]. For instance, cholesterol fulfills the cellular requirements for sterol in many insects, when it is obtained directly in the diet or derived from other sterols such as phytosterols; however, other species such as Drosophilu pachea [S], Epiluchnn vurivestis [6], and A f f a cephalofes isthrnicoZu [7] may use unusual sterols as their principal tissue sterols (ie, A7-, A'-, and A5!…”
Section: Introductionmentioning
confidence: 99%
“…As phytosterols play an important role in sterol metabolism and ecdysteroid production [8,10,[23][24][25][26], the ingestion of exogenous sterols is essential for structural and metabolic components. Sterols seem to be absorbed mainly in the midgut, particularly in phytophagous species [27,28], moving quickly through mucosal cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, all phytophagous insects studied to date rely on exogenous sterol for growth, reproduction and development [6,7]. Many phytophagous insects are able to convert phytosterols in cholesterol through the dealkylation of compounds containing 28 to 29 carbon atoms, such as desmosterol, campesterol, brassicasterol, fucosterol, and sitosterol [8][9][10]. However, honeybees are unable to perform this conversion [11,12].…”
Section: Introductionmentioning
confidence: 99%